2022
DOI: 10.1177/11207000221112579
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of hemiarthroplasty versus dynamic hip screw fixation for intertrochanteric femoral fractures: a systematic review

Abstract: Introduction: Intertrochanteric fractures are predominantly treated by dynamic hip screw (DHS) fixation. However, recent evidence has found acceptable clinical results following hemiarthroplasty for these fractures. Thus, a systematic review was conducted to compare hemiarthroplasty with DHS fixation for intertrochanteric fractures. Methods: A computerised search was performed, using the databases Medline, EMBASE, CINAHL and the Cochrane Central Register of Controlled Trials, with supplementation from Google S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…In this study, the mean time of full weight bearing was 5.36 ± 1.49 days, while in the studies by Sancheti et Hongku et al conducted a systematic review to compare the efficacy of osteosynthesis (dynamic hip screw, proximal femoral nail) and bipolar hemiarthroplasty and showed that dynamic hip screw and PFN had a significantly higher risk of operative failure compared with bipolar hemiarthroplasty in unstable intertrochanteric fractures in elderly patients [28]. Chowdhury et al did a systematic review to compare hemiarthroplasty and DHS fixation for intertrochanteric fractures in elderly patients [29]. They found that at 12 months, hemiarthroplasty led to significantly higher Harris Hip Scores and allowed patients to start bearing weight sooner than with DHS fixation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the mean time of full weight bearing was 5.36 ± 1.49 days, while in the studies by Sancheti et Hongku et al conducted a systematic review to compare the efficacy of osteosynthesis (dynamic hip screw, proximal femoral nail) and bipolar hemiarthroplasty and showed that dynamic hip screw and PFN had a significantly higher risk of operative failure compared with bipolar hemiarthroplasty in unstable intertrochanteric fractures in elderly patients [28]. Chowdhury et al did a systematic review to compare hemiarthroplasty and DHS fixation for intertrochanteric fractures in elderly patients [29]. They found that at 12 months, hemiarthroplasty led to significantly higher Harris Hip Scores and allowed patients to start bearing weight sooner than with DHS fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Our choice of hemiarthroplasty as a surgical procedure was driven by multiple factors, including patient age, presence of CKD, delayed presentation, and the fact that hemiarthroplasty provides better functional outcomes and has a shorter time to weightbearing compared to other procedures, such as the dynamic hip screw [14]. In a cohort of more than 70 000 patients who underwent surgery for femoral neck fractures, Wang and Bhattacharya reported that 95% of patients underwent hemiarthroplasty.…”
mentioning
confidence: 99%